2018
DOI: 10.2147/copd.s178068
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of neutrophil-to-lymphocyte ratio in COPD: a systematic literature review

Abstract: COPD is characterized by a pulmonary and systemic inflammatory process. Several authors have reported the elevation of multiple inflammatory markers in patients with COPD; however, their use in routine clinical practice has limitations. The neutrophil-to-lymphocyte ratio (NLR) is a useful and cost-effective inflammatory marker derived from routine complete blood count. We performed a systematic literature review using the PRISMA statement. Twenty-two articles were included, recruiting 7,601 COPD patients and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 65 publications
2
57
2
1
Order By: Relevance
“…Physiological response of circulating leukocytes to stress factors is an increase in numbers of neutrophils and a relatively lower count of lymphocytes and the ratio between these two subgroups (neutrophil‐to‐lymphocyte ratio—NLR) has been recently used to monitor the process of inflammation in many diseases such as lung cancer, colorectal cancer, end‐stage renal disease and acute coronary syndrome . Calculating NLR is easy and rapid since only complete blood count is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological response of circulating leukocytes to stress factors is an increase in numbers of neutrophils and a relatively lower count of lymphocytes and the ratio between these two subgroups (neutrophil‐to‐lymphocyte ratio—NLR) has been recently used to monitor the process of inflammation in many diseases such as lung cancer, colorectal cancer, end‐stage renal disease and acute coronary syndrome . Calculating NLR is easy and rapid since only complete blood count is needed.…”
Section: Introductionmentioning
confidence: 99%
“…14 Physiological response of circulating leukocytes to stress factors is an increase in numbers of neutrophils and a relatively lower count of lymphocytes and the ratio between these two subgroups (neutrophil-to-lymphocyte ratio-NLR) has been recently used to monitor the process of inflammation in many diseases such as lung cancer, colorectal cancer, end-stage renal disease and acute coronary syndrome. [16][17][18][19][20][21][22] Calculating NLR is easy and rapid since only complete blood count is needed. The test is based on the physiological response of circulating leukocytes to precipitating stress factors, with increased numbers of neutrophils and fewer lymphocytes, resulting in an increased NLR in periods of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated the usefulness of NLR to discriminate patients with pulmonary tuberculosis from patients with bacterial community‐acquired pneumonia (Yoon et al ., ). Another study showed that elevation of the NLR is associated with the diagnosis of acute exacerbation of chronic obstructive pulmonary disease (Pascual‐González et al ., ). Sunbul et al .…”
Section: Discussionmentioning
confidence: 97%
“…Chronic obstructive pulmonary disease (COPD) is a global health problem and the third leading cause of mortality worldwide. 1,2 COPD is a common disease characterized by improperly reversible airflow limitation and alveolar abnormalities. 1,2 The most important risk factors for COPD are smoking, air pollution, age, tuberculosis exposure, socioeconomic status and additionally geographical differences.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 COPD is a common disease characterized by improperly reversible airflow limitation and alveolar abnormalities. 1,2 The most important risk factors for COPD are smoking, air pollution, age, tuberculosis exposure, socioeconomic status and additionally geographical differences. 3 Around 400 million people live in high altitude (>1500 meters above sea-level) and this geographical altitude is associated with COPD prevalence, and adaptation mechanism of these patients.…”
Section: Introductionmentioning
confidence: 99%